PENGARUH SUBSTITUSI SUSU KEDELAI TERHADAP KUALITAS KUE LAPIS MALAYSIA - Qisthi, Puti Mizani; Syarif, Wirnelis; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
This research was motivated by the utilization of soy milk as much as 25%, 50% and 75% in the processing layer cake of malaysia. This type of research used the methode of random design complete with three repetitions. The data used were primary data sourced from 30 semi-trained panelists by proposed the organoleptic test format to see quality of the volume, shape, colour, aroma, texture and taste. Analyze data used ANAVA, if Fcount > Ftable then continued with Duncan test. The results showed there was significant influence to the quality of layer cake of malaysia that is on the quality of flavor soy milk. The quality of the volume expands, forms arectangle 8x1x6 cm, neatly shape, same shape, pink color, soft green color, soft yellow color, vanila aroma, soft texture and sweet taste wasn’t affect the quality of the layer cake of malaysia. The best present on the percentage of used of the soy milk 25%.Key word : Soy Milk, Layer Cake of Malaysia, Quality.